REMOTE WORK AS A FORM OF LABOUR ORGANISATION UNDER MARTIAL LAW - Vyshnovetska, Svitlana; Kolonska, Viktoriya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to identify the features of remote work as a temporary form of labour organisation under martial law. Research methods: documentary analysis and synthesis, cognitive and analytical methods, as well as methods of systematisation and generalisation. Results: the features of remote work as a form of labour organisation under martial law are determined. Discussion: the authors advocate a position that application of the remote form of labour organisation under martial law is the right, not the obligation of the employer, which independently determines the most favourable conditions for carrying out its business activity. The employee could insist on application of such form of labour organisation for him or her if it is possible depending on the performed work and if the employer has the appropriate resources and means for this. In determining the reasonable balance between the interests of the employer and the employee, the Supreme Court proceeds from the fact that the employer’s right to apply objective and reasonable changes in the organisation of production and labour of the enterprise prevails over the private interests of the employee. The remote work applied under martial law involves the temporary performance of the labour function of the employee working under a regular employment agreement outside a stationary workplace. In this case, the employee is a subject to the internal labour regulations and works within the working hours established by these regulations. Under martial law the remote work as a temporary form of labour organisation has its own peculiarities, which are shown, in particular, in a procedure and the conditions of its application. There are peculiarities of introducing this form of labour organisation for certain categories of the employees. For example, the civil servants and the employees of state bodies could work remotely during martial law by decision of their management only on the territory of Ukraine. The work of these persons outside Ukraine is allowed only in the case of a business trip, which is formalised in accordance with the established procedure.